Accuracy assessment of a novel image-free handheld robot for Total Knee Arthroplasty in a cadaveric study. Issue 1 (1st January 2018) - Casper, Michael; Mitra, Riddhit; Khare, Rahul; Jaramaz, Branislav; Hamlin, Brian; McGinley, Brian; Mayman, David; Headrick, Jeff; Urish, Kenneth; Gittins, Mark; Incavo, Stephen; Neginhal, Vivek
Abstract: Surgical navigation has been shown to improve the accuracy of bone preparation and limb alignment in total knee arthroplasty (TKA). Previous work has shown the effectiveness of various types of navigation systems. Here, for the first time, we assessed the accuracy of a novel imageless semiautonomous handheld robotic sculpting system in performing bone resection and preparation in TKA using cadaveric specimens. In this study, we compared the planned and final implant placement in 18 cadaveric specimens undergoing TKA using the new tool. Eight surgeons carried out the procedures using three types of implant designs. A quantitative analysis was performed to determine the translational, angular, and rotational differences between the planned and achieved positions of the implants. The mean femoral flexion, varus/valgus, and rotational error was −2.0°, −0.1°, and −0.5°, respectively. The mean tibial posterior slope, and varus/valgus error was −0.2°, and −0.2°, respectively. We obtained higher flexion errors for the femoral implant when using cut-guides as compared to using a bur for cutting the bones. The image-free robotic sculpting tool achieved accurate implementation of the surgical plan with small errors in implant placement. Future studies will focus on determining how well the accurate implant placement translates into a clinical and functional benefit for the patient.